2023
DOI: 10.3390/s23146423
|View full text |Cite
|
Sign up to set email alerts
|

Efficient-Lightweight YOLO: Improving Small Object Detection in YOLO for Aerial Images

Abstract: The most significant technical challenges of current aerial image object-detection tasks are the extremely low accuracy for detecting small objects that are densely distributed within a scene and the lack of semantic information. Moreover, existing detectors with large parameter scales are unsuitable for aerial image object-detection scenarios oriented toward low-end GPUs. To address this technical challenge, we propose efficient-lightweight You Only Look Once (EL-YOLO), an innovative model that overcomes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 44 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…26 However, large kernel convolutions also unavoidably increase the model's computational complexity. To address the problem of model lightening in aerial images, EL-YOLO 27 solves the problem of positive and negative sample imbalance by improving the loss function. Deng et al 28 improved YOLOv5s using a lightened backbone and proposed a lightened model LAI-YOLOv5s.…”
Section: Object Detection Algorithms In Aerial Imagesmentioning
confidence: 99%
“…26 However, large kernel convolutions also unavoidably increase the model's computational complexity. To address the problem of model lightening in aerial images, EL-YOLO 27 solves the problem of positive and negative sample imbalance by improving the loss function. Deng et al 28 improved YOLOv5s using a lightened backbone and proposed a lightened model LAI-YOLOv5s.…”
Section: Object Detection Algorithms In Aerial Imagesmentioning
confidence: 99%
“…It can be seen that the performance of our algorithm improves more significantly on small targets. We conducted comparative experiments involving prominent object detection algorithms on the VisDrone dataset, including YOLOv3 [44], YOLOv4 [45], YOLOv5l, YOLOv6s [46], YOLOv8s [47], Cascade R-CNN, RetinaNet, TPH-YOLOv5, PicoDet [48], PP-YOLOE [49], and EL-YOLOv5s [50]. By referring to the data presented in Table 8, it is evident that our proposed algorithm surpasses these models in terms of performance.…”
Section: Ablation Experimentsmentioning
confidence: 99%
“…Small target detection techniques 21 , 22 are an important research direction in computer vision aimed at addressing the problem of detecting and locating small objects in images or videos. Several optimization methods 23 , 24 based on existing object detection algorithms have been proposed to reduce the cases of missed detection and false detection for small targets, thereby improving the detection performance of small targets. Research has shown that data augmentation 25 , 26 can improve the detection performance of small targets by addressing the issues of low resolution, limited dataset quantity, and uneven distribution.…”
Section: Introductionmentioning
confidence: 99%